Kutipan Risalah Lelang Eksekusi dalam Proses Peralihan Hak bagi Pemenang Lelang pada Kantor Pelayanan Kekayaan Negara dan Lelang Makassar - Purwoko, Agung (CV. Social Politic Genius (SIGn), 2023)
This study aims to determine the process of implementing execution auctions, the issuance of Excerpts from the Auction Minutes, and the process of transferring rights to auctioned objects, as a form of legal protection for the Auction Winner carried out by the Makassar State Assets and Auction Service Office. The type of research used is empirical legal research with a quantitative descriptive approach. This research was conducted at the Makassar State Assets and Auction Service Office. Data collection techniques used in this study were questionnaires, documentation, and literature study. The data analysis technique used was quantitative data analysis. The results showed that the Makassar State Assets and Auction Service Office, in carrying out the auction and issuing the Excerpts from the Auction Minutes, has complied with the provisions of the applicable laws and regulations and has been running effectively. The implementation of auctions that have been carried out in accordance with the regulations cannot be canceled; this is a form of guarantee of legal certainty for all parties. It is expected that Sellers, Auction Officials, and Auction Buyers will be more careful, thorough, meticulous, and understand all regulations related to the implementation of auctions to avoid potential legal loopholes that may arise and could nullify the auction.